A prospective feasibility study of sentinel node biopsy by modified Indigocarmine blue dye methods after neoadjuvant chemotherapy for breast cancer. Issue 4 (April 2015) - Kida, K.; Ishikawa, T.; Yamada, A.; Shimizu, D.; Tanabe, M.; Sasaki, T.; Ichikawa, Y.; Endo, I.
Abstract Background Although sentinel lymph node biopsy (SLNB) is a standard staging method for assessing nodal status of breast cancer patients, SLNB after neoadjuvant chemotherapy (NAC) remains controversial. The aim of this study was to validate the practicality and accuracy of SLNB by our modified Indigocarmine blue dye methods following NAC. Methods One hundred consecutive cases with breast cancers treated by NAC were enrolled in this study. After NAC, all patients underwent SLNB performed by our modified Indigocarmine blue dye methods without radioisotope, followed by back-up axillary lymph node dissection (ALND). Results Sentinel nodes (SNs) were identified in 94 cases (identification rate, 94%); the accuracy was 94.7% (89/94 cases); and the false negative rate (FNR) 13.5% (5/37 cases). For cases with vs. without clinically evident metastatic nodes before NAC, the identification rate was 92.4% (61/66 cases) vs. 97.1% (33/34 cases); the accuracy 91.8% (56/61 cases) vs. 97.0% (32/33 cases) and the FNR 16.1% (5/31 cases) vs. 0% (0/6 case), respectively. There were six patients without identified SNs, three of them had metastatic nodes. False negatives occurred in five cases; in four, fewer than two sentinel nodes had been removed. Conclusion Following NAC, the accuracy of SLNB by modified Indigocarmine blue dye methods is adequate compared with other tracers. In patients in whom no SNs have been identified, lymphatic metastasis is likely and therefore ALND is recommended. For patients with cN0 prior to NAC, SLNB by modified Indigocarmine blue dye methods is clinically feasible, though controversial for patients with positive nodes.